2017
DOI: 10.1111/bph.14065
|View full text |Cite
|
Sign up to set email alerts
|

WNT signalling: mechanisms and therapeutic opportunities

Abstract: At the same time as the mechanistic understanding of the WNT signalling system, with its family of 19 secreted lipoglycoproteins, 10 class Frizzled GPCRs (FZD 1-10 ), several single transmembrane-spanning receptors [LDL receptorrelated protein 5/6 (LRP5/6), ROR1/2, RYK and PTK7] and a plethora of extracellular modulators [Dickkopfs (DKKs), SFRPs, WIFs, etc.] at the core of the pathway, is improving it becomes obvious that targeting this system therapeutically comes both with great potential and substantial ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 13 publications
0
10
0
Order By: Relevance
“…Wnt signaling regulation of β-catenin plays critical role in variety of physiological processes (41). Previous studies have demonstrated that the expression level of β-catenin was upregulated in degenerative chondrocytes, resulting in loss of cartilage (42,43).…”
Section: Discussionmentioning
confidence: 99%
“…Wnt signaling regulation of β-catenin plays critical role in variety of physiological processes (41). Previous studies have demonstrated that the expression level of β-catenin was upregulated in degenerative chondrocytes, resulting in loss of cartilage (42,43).…”
Section: Discussionmentioning
confidence: 99%
“…The Wnt signaling pathway is a complex network of proteins best known for their roles in embryogenesis and cancer, but also involved in normal physiological processes in adult animals 56,57 . Wnt proteins bind to receptors of the Frizzled family and several co‐receptors such as low‐density lipoprotein receptor‐related proteins 5 and 6 (LRP5 and LRP6), Ryk, or Ror2 58,59 .…”
Section: Convergent Regulation Of Blood–brain Barrier Integrity By In...mentioning
confidence: 99%
“…The Wnt signaling pathway is widely found in invertebrates and vertebrates and is a highly evolutionarily conserved signaling pathway. It plays a crucial role in the early development of embryos, organogenesis, and maintenance of normal physiological functions in adults ( Schulte and Bryja, 2017 ; Jean LeBlanc et al, 2019 ; Routledge and Scholpp, 2019 ).…”
Section: The Intracellular Trafficking Of Wnt Signalingmentioning
confidence: 99%
“…The above studies suggest that the ischemic penumbra still has great therapeutic potential for neuroprotection. The Wnt pathway is part of an evolutionarily conserved intracellular signal transduction cascade that regulates multiple processes crucial for cell proliferation, differentiation, migration, and fate decision during development ( Schulte and Bryja, 2017 ; Eubelen et al, 2018 ). Recently, several studies have reported the mechanism by which Wnt/β-catenin signaling is regulated in the adult brain and serves as an endogenous protective mechanism against the central nervous system (CNS) diseases ( Schulte and Bryja, 2017 ; Menet et al, 2020 ; Cheng et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation